Intravenous injection of cyclophilin A realizes the transient and reversible opening of barrier of neural vasculature through basigin in endothelial cells - Narumi Nakada-Honda (Nature Portfolio, 2021)
Abstract Neural vasculature forms the blood–brain barrier against the delivery of systemically administered therapeutic drugs into parenchyma of neural tissues. Therefore, procedures to open the blood–brain barrier with minimal damage to tissues would lead to the great progress in therapeutic strategy for intractable neural diseases. In this study, through analyses with mouse in vitro brain microvascular endothelial cells and in vivo neural vasculature, we demonstrate that the administration of cyclophilin A (CypA), a ligand of basigin which is expressed in barrier-forming endothelial cells, realizes the artificial opening of blood–brain barrier. Monolayers of endothelial cells lost their barrier properties through the disappearance of claudin-5, an integral tight junction molecule, from cell membranes in a transient and reversible manner. Furthermore, the intravenous injection of a single dose of CypA into mice resulted in the opening of blood–brain barrier for a certain period which enabled the enhanced delivery of systemically administered doxorubicin into the parenchyma of neural tissues. These findings that the pre-injection of a single dose of CypA realizes an artificial, transient as well as reversible opening of blood–brain barrier are considered to be a great step toward the establishment of therapeutic protocols to overcome the intractability of neural diseases.